2021
DOI: 10.1088/1757-899x/1094/1/012159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Titanium Dioxide Nanoparticles on the Mechanical Strength of Epoxy Hybrid Composite Materials Reinforced with Unidirectional Carbon and Glass Fibers.

Abstract: The present work describes the development of hybrid epoxy composite reinforced with unidirectional carbon, glass fibers and nano-TiO2 powder in order to study some of its mechanical properties. Titanium dioxide (TiO2) were dispersed in epoxy with different weight fractions (1, 3, and 5 wt. %) using sonication. Composite materials under study have been prepared by reinforcing the resulted nanocomposite by three different layers of unidirectional carbon fibers and glass bidirectional fibers using hand lay-up te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The first point worth mentioning is that when the property is plotted as a function of NP, a better overlap can be seen for the two 28.4 m 2 /g curves, despite the particular processing parameters considered in each study [ 100 , 101 ], which the previous and traditional form of portraying data (in wt.%, as seen in Figure 1 ) did not show. Although the maximum on the property curves was seen before, the representation in Figure 4 clearly separates such maxima, bringing to evidence their dependence on the specific surface area.…”
Section: Particle Effects On Composite Thermomechanical Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The first point worth mentioning is that when the property is plotted as a function of NP, a better overlap can be seen for the two 28.4 m 2 /g curves, despite the particular processing parameters considered in each study [ 100 , 101 ], which the previous and traditional form of portraying data (in wt.%, as seen in Figure 1 ) did not show. Although the maximum on the property curves was seen before, the representation in Figure 4 clearly separates such maxima, bringing to evidence their dependence on the specific surface area.…”
Section: Particle Effects On Composite Thermomechanical Propertiesmentioning
confidence: 91%
“…The doubtful confidence on the effect of added particle content can be illustrated by referring to the two different authors ( Table 2 , [ 100 , 101 ]) that explored similar 50 nm TiO 2 particles (SSA of 28.4 m 2 /g) seeking to improve the tensile strength performance but used a different added particle content range. As seen in Figure 1 , the resulting curves do not seem to match each other, even for the common particle content.…”
Section: Particle Effects On Composite Thermomechanical Propertiesmentioning
confidence: 99%
“…Papanicolaou et al [26] Noticed that adding of nano TiO2 in the epoxy matrix led to a decrease in the flexural modulus, and the flexural strength decreases with the increase of filler weight fraction. Abass et al [27] showed that the addition of 3% wt. TiO2 nanoparticles to the epoxy composite reinforced with unidirectional carbon and glass fibers enhances its mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…, with epoxy resin on tensile properties, The results showed that the tensile strength magnitude increased with increasing AC content up to 15 % wt., then it decreased at 40 % wt. Basim A. Abass et al [16] investigated the mechanical properties of a hybrid epoxy composite strengthened by TiO 2 nano powder, glass fibbers and unidirectional carbon fiber. Different weight percentages of TiO 2 nano-powder was dispersed in epoxy using sonication.…”
Section: Introductionmentioning
confidence: 99%